The Transformational Nature of our Work: An Interview with Karen Aceves, Amparo Diaz, and Guadalupe Pinto (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
This interview explores how competency-based education and learning recognition can serve as transformative tools for equity, access, and economic mobility. Nan Travers and Alan Mandell speak with Karen Aceves, Amparo Diaz, and Guadalupe Pinto about statewide policy innovation in California and the development of a groundbreaking Ag Tech workforce program rooted in the lived realities of farmworkers in the Central San Joaquin Valley.